Optimization of Wireless Power Transfer Configuration for High Efficiency Achievement - Ponniran, Asmarashid; Hashim, Hazem (Evolution in Electrical and Electronic Engineering, 2020)
This paper discusses the efficiency improvement of a wireless power transfer system based on parameters design optimization. The wireless power transfer system is designed to operate at higher frequencies in order to reduce the component sizing as well as power density improvement. Configuration of the wireless power transfer system, i.e., transmitter and receiver coil are designed based on proper resonance frequency. The principle of the parameters design optimization is based on the single transmitter – multiple receiver coil configuration which reduces the system complexity and magnetic resonant method implementation which amplify the energy transferred between the coils. Simulation using ANSYS Maxwell and ANSYS Simplorer software shows the system efficiency is at the peak at the resonance frequency of 13.5571 MHz with a total power of 18 W delivered at a distance of 5 mm. Furthermore, the efficiency of AC – DC converter and high frequency DC – AC converter considered for power conversions are 99.81% and 99.51% respectively. Therefore, the maximum power transfer efficiency of the considered wireless power transfer system configuration is determined through this study.